2006
DOI: 10.1007/s11881-006-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and linguistic influence on brain organization for language and possible consequences for dyslexia: A review

Abstract: Current neuroimaging and neurophysiologic techniques have substantially increased our possibilities to study processes related to various language functions in the intact human brain. Learning to read and write influences the functional organization of the brain. What is uni-13 individual studies mentioned in this review, the readers are referred to the individual papers quoted. However, some short presentations and explanations to abbreviations used are given here. With positron emission tomography (PET) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 185 publications
(183 reference statements)
0
11
0
Order By: Relevance
“…The success of this adaptation suggests that the same framework can be applied to understanding reading skill across a wide variety of languages, despite gross differences in their surface properties. This is a critical first step in providing a mechanistic explanation of many cross-linguistic phenomena, including the differential impact of factors that predict reading success (McBride-Chang, Chao, Liu, et al, 2005; Shu, Peng, & McBride-Chang, 2008), differences in the prevalence of developmental disorders of reading (Johansson, 2006; Shu, McBride-Chang, Wu, & Liu, 2006; Shu, Meng, Chen, Luan, & Cao, 2005) and patterns of reading disorder subsequent to brain injury (Bi, Han, Weekes, & Shu, 2007; Jefferies, Sage, & Ralph, 2007; Woollams, Lambon Ralph, Plaut, & Patterson, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…The success of this adaptation suggests that the same framework can be applied to understanding reading skill across a wide variety of languages, despite gross differences in their surface properties. This is a critical first step in providing a mechanistic explanation of many cross-linguistic phenomena, including the differential impact of factors that predict reading success (McBride-Chang, Chao, Liu, et al, 2005; Shu, Peng, & McBride-Chang, 2008), differences in the prevalence of developmental disorders of reading (Johansson, 2006; Shu, McBride-Chang, Wu, & Liu, 2006; Shu, Meng, Chen, Luan, & Cao, 2005) and patterns of reading disorder subsequent to brain injury (Bi, Han, Weekes, & Shu, 2007; Jefferies, Sage, & Ralph, 2007; Woollams, Lambon Ralph, Plaut, & Patterson, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Tan et al (Siok, Perfetti, Jin, & Tan, 2004; Siok, Niu, Jin, Perfetti, & Tan, 2008) explored the structural-functional basis of development dyslexia in Chinese readers using functional MRI, and found that the biological basis of impaired reading was dependent on culture. For readers of alphabetic writing systems (e.g., English), dyslexia was associated with dysfunction of the left temporoparietal and occipitotemporal regions (Aylward et al, 2003; Horwitz, Rumsey, & Donohue, 1998; Johansson, 2006; Shaywitz et al, 1998; Sun, Lee, & Kirby, 2010; Temple et al, 2003). For readers of logographic writing systems (e.g., Chinese), impaired reading was associated with structural and functional abnormalities of the left middle frontal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Code-switching is taken as a sign of bilingual proficiency (Poplack, 1980 ; Lucas and Valli, 1992 ), and it is heavily used as an in-group sociolinguistic phenomenon in highly bilingual communities (Bhatt and Bolonyai, 2011 ). Nevertheless, it cannot be said that young bilingual children's languages are completely separate (Unsworth, 2013 ). We conclude, then, that the best tack to take toward understanding the development of bilingualism is to model the adult state and to see how children move toward achieving this state.…”
Section: Introductionmentioning
confidence: 99%